PJMHS 2022
DOI: 10.53350/pjmhs221692
|View full text |Cite
|
Sign up to set email alerts
|

Radish (Raphanus Sativus): Potential antioxidant role of bioactive compounds extracted from radish leaves - A review

Abstract: Radish (Raphanus Sativus) used against many toxicants as a natural drug, is a worldwide grown cruciferous root crop with root part the main edible organ and leave part, which in dried form are effective as functional foods. Radish (Raphanus Sativus) that exhibits variety of colors has rich content of vitamins, phenolic compounds, dietary fiber and Phyto-anthocyanin. Based on physico-chemical, nutritional, antioxidant and microbiological properties radish leaves are more nutritionally rich than roots. Leaves a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Radish leaves are believed to have nutritional and medicinal value, particularly fueled by their antioxidant activity. Studies have investigated their potential as functional foods [ 34 ]. Given their reported nutritional and medicinal properties, this study explored the effects of radish leaves on human health.…”
Section: Discussionmentioning
confidence: 99%
“…Radish leaves are believed to have nutritional and medicinal value, particularly fueled by their antioxidant activity. Studies have investigated their potential as functional foods [ 34 ]. Given their reported nutritional and medicinal properties, this study explored the effects of radish leaves on human health.…”
Section: Discussionmentioning
confidence: 99%
“…Radish leave and root sprouts are considered plant sources rich in nutrients and chemical compounds that are a significant source of flavonoids (in particular, anthocyanin), as well as β-carotene and vitamin C, and they can be considered as a raw material for developing a healthy diet [22][23][24]. It is worth noting what was mentioned by [25] about the importance of radish leaves, particularly as more critical and valuable than the root, as they are the primary source of phenols and flavonoids and can also catch free radicals. His research paper identified the antioxidant compound Rutin in radish leaves only.…”
Section: Introductionmentioning
confidence: 99%